Toxicity nanoinsecticide based on clove essential oil against Tribolium castaneum (Herbst) - Ikawati, Silvi (J Pestic Sci, 2021)
This study aimed to characterize nanoparticles loaded with clove (Syzygium aromaticum) essential oil-based polyethylene glycol (PEG) and to know their insecticidal activity against red flour beetle (Tribolium castaneum). The nanoparticles have irregular shapes in good dispersion. The nanoformulation could not enhance clove oil contact toxicity to T. castaneum, but could protect the oil from degradation and evaporation while simultaneously allowing sustained release, as indicated by the continued high toxicity for 16 weeks of storage.